Determinación de antocianinas y valor nutricional de los tenebrios (tenebrio molitor) alimentados con dietas enriquecidas con maíz morado (Zea Mays L.) - Intriago Sánchez, Thalía Cerela (2014)
Purple corn traditionally been considered as a food source, nowadays known to contain large amounts of, especially natural antioxidants anthocyanins; For this reason, this paper aims to encourage the feeding of insectivorous animals by a natural food supplement based on beetle larvae (Tenebrio molitor) fed cornmeal morado.-